Self-esteem and oral health-related quality of life of women with periodontal disease - A cross-sectional study - Rohina Shamim; Rashmita Nayak; Anurag Satpathy; Rinkee Mohanty; Naina Pattnaik (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study is to assess the effect of periodontal disease on self-esteem and oral health-related quality of life (OHRQoL) in women. Materials and Methods: A cross-sectional study was conducted among 522 women (mean age − 38.92 ± 14.3 years). Oral hygiene status, plaque level, gingival inflammation, probing depth, and periodontal status were assessed. The self-esteem was assessed using a Rosenberg Self-esteem Scale, and the OHRQoL was measured using a 14-item oral health impact profile (OHIP-14) questionnaire. Results: Younger, employed women with higher income had significantly better OHRQoL and self-esteem. Women with healthy periodontium had better OHRQoL. Probing depth and community periodontal index scores were found to have a significant positive correlation with most of the sub-scale items and total OHIP-14 score in women with low self-esteem. Women with good OHRQoL and normal self-esteem were seen to be maintaining significantly better oral hygiene. No such statistically significant difference was observed in women with low self-esteem. Multiple regression analysis for the prediction of OHIP-14 score indicated that the best model included probing depth as the only statistically significant predictor (P = 0.002). Conclusion: Periodontal disease has a significant negative impact on self-esteem and OHRQoL in women.